Sosialisasi Penggunaan Kosmetik Racikan di Kalangan Mahasiswa ITKeS Muhammadiyah Sidrap - Wahyuni L Ode; Fadhillah Syam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Cosmetics are materials or preparations that are used on the outside of the human body (epidermis, hair, nails, lips and external genitalia) or on the teeth and mucous membranes of the mouth especially to clean, perfume, change appearance and/or improve body odor or protect or maintain body. in good condition. The purpose of socializing the use of concoction cosmetics among ITKeS Muhammadiyah sidrap students. The method used in this community service is lectures and questions and answers about the Selection and Use of Safe Concoction Cosmetics. From the results of community service before counseling was held about the Selection and Use of Safe Concoction Cosmetics at ITKeS Muhammadiyah Sidrap. it was found that the knowledge category was quite good (23.3%) with a good category (76.7%, and after the counseling was carried out the category. good knowledge became (100%). The results of students' knowledge about cosmetic concoction of Respondent 4 (8.70%) in the good category, 37 respondents (80.43%) in the medium category, and 5 respondents in the less category (10.86%).